FINANCIAL INCLUSION, INSTITUTIONAL QUALITY, AND POVERTY REDUCTION IN NIGERIA - Rashidat Sumbola Akande; Hauwah K. K. AbdulKareem; Aminat Olayinka Olohunlana (Malete Journal of Accounting and Finance, 2024)
Poverty alleviation remains a global challenge and at the fore front of the economic development of developing economies like Nigeria. Although it has been established in literature that financial inclusion is crucial for poverty reduction, few studies have examined the role of institutional quality as an important determinant of poverty reduction. Hence, this study examines institutional quality and financial inclusion on poverty reduction in Nigeria. The paper is anchored on the Capability Approach and adopts the Human Development Index (HDI) as a proxy for poverty reduction as it measures basic human capabilities. With time series data from 1987 to 2022 the VECM is employed as the estimation technique given the established long-run relationship obtained from the ARDL bounds test cointegration technique. Findings reveal that in the short run, financial inclusion and institutional quality are statistically significant and positive for poverty reduction. In the long run, however, these relationships become insignificant. This study, therefore, elucidates on the opposing directions of financial inclusion and poverty alleviation in the country with institutional quality also shown to be vital. Consequently, financial inclusion and institutional quality are found to be necessary, but insufficient conditions for poverty reduction. Hence, while financial inclusion and good institutions are important in the short run, long-term poverty alleviation strategies must be comprehensive and multi-sectoral in approach to complement, consolidate, and sustain the poverty reduction potentials of financial inclusion and high-quality institutions.